Assessing the Relationships Between Gender, Years of Teaching Experience, and Proficiency in Test Construction Among Ghanaian Senior High School Teachers - Gunu, Ibrahim, Mohammed; Adam, Abu; Abdul-Waris, Mustapha (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigated the relationship between years of teaching experience, gender and proficiency in test construction skills among senior high school teachers in Ghana. Using a descriptive survey design, data was collected from 241 teachers selected through a multi-stage sampling procedure from four public senior high schools. A structured questionnaire employing a five-point Likert scale was administered via Google Forms to assess test construction practices. Analysis of Variance (ANOVA) revealed no statistically significant differences in test construction proficiency across different experience levels (F = 1.143, p = 0.332). However, chi-square analysis indicated significant gender differences in test construction practices (χ² = 5.306, p = 0.021). The findings challenge the assumption that teaching experience alone enhances test construction abilities and highlight the need for structured professional development programmes. Recommendations of the research include implementing comprehensive assessment training, establishing mentoring systems, and developing standardized test construction guidelines regardless of teaching experience.